2004
DOI: 10.2466/pms.99.2.392-402
|View full text |Cite
|
Sign up to set email alerts
|

Does Augmented Feedback from Pedometers Increase Adults' Walking Behavior?

Abstract: This study investigated whether feedback from pedometers motivated adults to increase their walking behavior. Participants (n =26) were enrolled in one of two 8-wk. "Walking for Fitness" classes. The study used a crossover design, such that Group 1 wore pedometers for the first 3 weeks (Feedback Condition) and sealed "disguised" pedometers for the last 3 weeks (No-feedback Condition). The order of feedback was reversed for Group 2. Analysis indicated that (a) neither group increased their walking behavior sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
3
26
1
Order By: Relevance
“…Permuted block randomization (with block size of four for two groups) was used to maintain a reasonable balance between the groups based on our plan to recruit 40 participants (randomly assigned 20 in each group). The justification for an 8-week intervention comes from a prior study (Eastep, Beveridge, Eisenman, Ransdell, & Shultz, 2004). Participants in the usual-care control group received written information regarding PA (e.g., exercise suggestions).…”
Section: Methodsmentioning
confidence: 99%
“…Permuted block randomization (with block size of four for two groups) was used to maintain a reasonable balance between the groups based on our plan to recruit 40 participants (randomly assigned 20 in each group). The justification for an 8-week intervention comes from a prior study (Eastep, Beveridge, Eisenman, Ransdell, & Shultz, 2004). Participants in the usual-care control group received written information regarding PA (e.g., exercise suggestions).…”
Section: Methodsmentioning
confidence: 99%
“…Currently however there are conflicting findings on the presence/absence of pedometer reactivity in adults (Matevey et al 2006;Behrens and Dinger 2007;Clemes et al 2008b). Eastep et al (2004) have suggested that if pedometer reactivity exists, it will dissipate within approximately two weeks of monitoring. By employing an extensive four-week monitoring frame, habitual activity levels are more likely to be captured.…”
Section: Discussionmentioning
confidence: 99%
“…To date, little research has investigated whether reactivity exists in adult populations when participants wear an unsealed pedometer and record daily step counts (7,12,17,21). Matevey et al (21) and Eastep et al (17) both reported minimal differences between unsealed and sealed (when the visible display of the pedometer is restricted) step counts, whereas Behrens and Dinger (7) reported no evidence of reactivity occurring in response to wearing an accelerometer and an unsealed pedometer.…”
mentioning
confidence: 95%
“…In the research outlined above (7,21,24,27,38), in the sealed condition, participants have all been aware that they were wearing a pedometer or a device that measures physical activity (17), which in itself may elicit some degree of reactivity. Only when participants are unaware that their activity levels are being monitored (termed covert monitoring) can a true investigation into reactivity be undertaken (6).…”
mentioning
confidence: 99%